HUBUNGAN BEBAN KERJA DENGAN KEPATUHAN PETUGAS DALAM PENANDAAN LOKASI (SITE MARKING) OPERASI DI RSUD SUMBERGLAGAH - Maya Safitri Rohmayani; Ike Prafita Sari; Siti Rachmah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Until now, High workload causes nurses to be disobedient in carrying out procedures, one of which is: site marking. Currently in hospitals the marking of surgical sites still receives very little attention and is considered a random event that rarely occurs. This research aims to determine the relationship between workload and officer compliance in marking locations (site marking) operation at Sumberglagah Regional Hospital. This research uses observational analytical research methods with research design cross sectional. The total sample was 44 respondents. The research was conducted in July - August 2024. The research results showed that almost half of them had a moderate workload with a low compliance level of 18 respondents (40.9%). Based on statistical test results Spearman Rank obtained p value = 0.001 < α = 0.05 with correlation coefisient (-0.766) thus indicating a strong relationship between workload and officer compliance in marking locations (site making) operation but shows the opposite direction of correlation. The negative direction of the correlation indicates that the heavier the workload, the more disobedient officers are in marking locations (site marking) operation. In this research, it is hoped that doctors and nurses will receive a clear division of duties in accordance with their respective duties and functions. Nurses who will take patients to surgery should verify and identify signs of the operation location before taking the patient to the operating room and operating room nurses should carry out verification and identification as well as record them on the available checklist sheet which is further enhanced to prevent unwanted events from occurring.